2017
DOI: 10.1007/s10461-017-1893-4
|View full text |Cite
|
Sign up to set email alerts
|

HIV Linkage to Care and Retention in Care Rate Among MSM in Guangzhou, China

Abstract: Quantifying HIV service provision along the HIV care continuum is increasingly important for monitoring and evaluating HIV interventions. We examined factors associated with linkage and retention in care longitudinally among MSM (n = 1974, 4933 person-years) diagnosed and living in Guangzhou, China, in 2008-2014. We measured longitudinal change of retention in care (≥2 CD4 tests per year) from linkage and antiretroviral therapy initiation (ART). We examined factors associated with linkage using logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In 2013, HIV treatment retention for 12, 24, and 60 months was 66%, 62%, and 44%, respectively [ 17 ]. These drop-out levels are comparable to the treatment retention of HIV-positive MSM and transwomen populations in other countries [ 18 , 19 ]. However, specific data about how HIV-positive MSM and waria in Indonesia are linked to and retained in care is scarce.…”
Section: Introductionsupporting
confidence: 60%
“…In 2013, HIV treatment retention for 12, 24, and 60 months was 66%, 62%, and 44%, respectively [ 17 ]. These drop-out levels are comparable to the treatment retention of HIV-positive MSM and transwomen populations in other countries [ 18 , 19 ]. However, specific data about how HIV-positive MSM and waria in Indonesia are linked to and retained in care is scarce.…”
Section: Introductionsupporting
confidence: 60%
“…Socio-demographic characteristics. Several socio-demographic factors associated with disparities in access to care may also be associated with inequalities in the HIV care continuum [11,14,16,[25][26][27][28]30]. We investigated biological sex, age (at the time of the survey), ethnicity (Han and other), religious beliefs, marital status, education level (primary school or below, secondary school, high school, and university or above), employment status (employed and unemployed), and type of medical insurance (none, New Rural Cooperative Medical Insurance (NRCMI), Urban Employees Basic Medical Insurance (UEBMI), and Urban Residents Basic Medical Insurance (URBMI)).…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous studies have indicated that socioeconomic status (SES), younger or older age, employment, education, area of residence, and health insurance were associated with HIV epidemics, HIV testing, maternal care, delays in HIV treatment, access to ART, attrition of ART, and even poorer treatment outcomes [11,14,[25][26][27][28]. However, there is a paucity of studies measuring the socioeconomic-related inequality in care for people living with HIV who are stable on ART, especially in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%
“…Men who have sex with men (MSM) have been identified as one of the key populations in the HIV epidemic. The prevalence of HIV among MSM in China has been rapidly and continuously increasing, especially in metropolitan cities such as Beijing, Guangzhou, and Chengdu [1][2][3]. The pooled prevalence of HIV infection among MSM soared from 1.4% in 2001 to 9.0% in 2013 [4], and transmissions between MSM accounted for 25.5% of the new HIV infections in 2017 [5].…”
Section: Introductionmentioning
confidence: 99%